How visible are we really? A sociotechnical exploration into the sustainability of digital scholarship collections - Van Wyk, Brenda; Du Toit, Adeline (COLLNET 2016, 2016)
Over and above quality teaching and learning, the status and prestige of higher education institutions depend on the quality, web visibility and accessibility of their research and scholarly communication. Universities and higher education institutions are knowledge intensive environments. Research and scholarship created here are institutional knowledge capital and must be managed as assets, allowing the institutions to derive a competitive edge in research and improved institutional stature. As such, knowledge capital must be managed in a way that will ensure return on investment. Scholarship found in dissertations, theses, proceedings and publications form part of this knowledge capital. Digitised institutional repositories are the preferred method for showcasing scholarship on the internet, thereby adding to the institution’s web visibility. Research repositories developed over the past twenty years to become sophisticated networked digital research collections. Traditional research institutions reap benefits from showcasing scholarship digitally in open access repositories, and peer reviewed academic journals. Institutions with well-developed repositories rank consistently higher on webometric ranking sites, such as Ranking Web of Universities. However, not all higher education institution sectors have benefited equally from repository and scholarship curation developments. Globally, recent research indicates that valuable research output originates from both public and private higher education institutions, but these are not archived and curated sustainably in all circumstances. Web analysis indicates that research done in some comprehensive- and universities of technology, as well as most private higher education institutions in Southern Africa lack web visibility and discoverability. Coincidentally, Southern African private higher education institutions rank significantly lower than comparative public counter parts. Poor scholarship curation and lack of research visibility deter these institutions from taking their rightful place in higher education and higher education research communities. Where research collections are not managed sustainably as knowledge capital, full return on investment will not be possible. Previous reported research focused mainly on technical processes of scholarship curation, and not so much on knowledge management aspects impacting on sustainable curation practices. Building on previous research results, this paper explores a sociotechnical approach to improved sustainability of scholarship curation. This study investigated digital scholarship curation trends in a purposefully selected target group of private and public higher education institutions in Southern Africa. Empirical questionnaire results were triangulated with corresponding webometric ranking analysis pertaining to the target group. Identified gaps in current scholarship curation trends explain the poor web visibility in the target group. Results confirm that there is a lack of awareness and knowledge regarding scholarship curation in the target group. Findings are that particularly private higher education lack understanding of how scholarship curation in open access repositories can benefit their institutional stature and reputation. These trends are reflected in data analysis of these institutions on web ranking databases, where private institutions rank significantly lower. Although public higher education institutions in the target group ranked higher on webometric databases than their private counter parts, here too serious sustainability risk factors have been identified in managing their scholarship in digital research repositories.
Keywords: Digital scholarship curation; Web visibility; Webometrics; Sustainability